Severe Visual Impairment and Blindness among Children in Mbarali district, Southern Tanzania: Prevalence and types (Tanzania Medical Journal, 2017)
BackgroundThe prevalence of severe visual-impairment (SVI) and blindness (BL) in children is related to under-five mortality rates which have reduced in Tanzania. The prevalence and types of SVI-and-BL in Mbarali district is not known. We aimed to determine the prevalence and the types of SVI-and-BL among children in Mbarali district, Mbeya, Tanzania.MethodsA population based cross-sectional survey was conducted from March 2016 to April 2016 among children less than 16 years in all villages of Mbarali district. A total of 113 village health workers one from each village were trained to identify children with poor vision of <6/60 in the better eye. A total of 247 children were identified and brought to an agreed examination center within the ward, for examination by an ophthalmologist and optometrist. Clinical examination involved assessment of visual-acuity, anterior and posterior segments of the eye and ocular-motility. The cause of visual loss and the type of visual-impairment or blindness was determined using the WHO classification system. All information was recorded on the WHO-recording form for severe visual-impairment or blindness. Population data were obtained from the 2010 census. Data were analyzed using SPSS version 20 and were summarized by frequency tables. Chi -square test was used to test for statistical significance of an association between variables.ResultsKey Informants identified 247 children of whom 66 were found to be SVI or BL. The overall prevalence of SVI-and-BL was 0.05% (95%Cl 0.04–0.06%). The prevalence of SVI/BL among <5 years was 0.04% (95%Cl 0.02–0.06%) and for children aged 5-15 years was 0.05% (95%Cl 0.04–0.07%). Seventy per-cent of SVI-or-BL children were aged 5-15 years. The prevalence of SVI-and-BL among boys was 0.04% (95%Cl 0.03–0.06%) while that of females was 0.05% (95%Cl 0.03–0.07%). The causes of SVI- and-BL were lens related (27%), refractive error (15%) and corneal related conditions (13%). Severe visual-impairment or blindness was treatable (65%), preventable (9%) and unavoidable (25.7%).ConclusionThe prevalence of severe visual impairment and blindness in Mbarali district is lower than previous estimates by the WHO, mostly treatable, commoner among girls aged >5 years. It is likely that preventable SVI and blindness have been reduced by successful child survival programs. In order to eliminate avoidable SVI-and-BL, Tertiary eye-services for children need be established at Mbeya Zonal Referral hospital to combat treatable SVI-and-BL.